Solar System Courseware / Ahmad Danial Man Abisuffian - Man Abisuffian, Ahmad Danial (2023)
The solar system can be a difficult topic for some students to master, as it involves a lot memorization of numbers and mathematical formulas. This study discusses on the development of a courseware program developed to aid teachers and schools on teaching students about the solar system, through the Solar System Courseware. The courseware is developed so that it can run on operating systems installed by the most devices, which is Microsoft Windows, in order to target a larger userbase. The objective of the project is to develop a courseware program about the Solar System, based on Chapter 12 in the Form 2 KSSM Science Textbook in order to provide a learning aid for the students to learn about the topic. The project is designed to be entertaining and simple as to attract the attention of young students so that they would be interested in learning about the topic and develop an interest for it. The courseware evaluation was done by one expert who is a lecturer of UiTM Kuala Terengganu in order to assess the viability of the courseware based on the opinion of an educator. From the evaluation conducted, the courseware performed well in order to deliver its proposed functions.